2016
DOI: 10.1084/jem.20160189
|View full text |Cite
|
Sign up to set email alerts
|

Siglec-H protects from virus-triggered severe systemic autoimmunity

Abstract: Siglec-H is a key negative regulator of the type I interferon pathway, reducing the incidence of autoimmunity after viral infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 75 publications
(113 reference statements)
0
26
1
Order By: Relevance
“…CTLA-4, PD-1, LAG-3, TIM3, VISTA, TIGIT, FcγRIIb, certain Siglecs) are expressed on the surface of T and B cells to curtail excessive immune responses, both normal and anti-self. Deficiency of some of these molecules leads to autoimmunity, providing strong evidence that autoreactive lymphocytes are present in the peripheral repertoire but are normally under control 2328 . Importantly, blockade of these inhibitory molecules by specific antibodies has recently emerged as an effective anti-tumor approach, referred to as “checkpoint immunotherapy” 29 .…”
Section: Activation Of Escaped Autoreactive Cellsmentioning
confidence: 99%
“…CTLA-4, PD-1, LAG-3, TIM3, VISTA, TIGIT, FcγRIIb, certain Siglecs) are expressed on the surface of T and B cells to curtail excessive immune responses, both normal and anti-self. Deficiency of some of these molecules leads to autoimmunity, providing strong evidence that autoreactive lymphocytes are present in the peripheral repertoire but are normally under control 2328 . Importantly, blockade of these inhibitory molecules by specific antibodies has recently emerged as an effective anti-tumor approach, referred to as “checkpoint immunotherapy” 29 .…”
Section: Activation Of Escaped Autoreactive Cellsmentioning
confidence: 99%
“…DAP12 knockdown restricted PRRSV infection by increasing type I IFN production ( Figures 5A-D), which was similar to the effects of poSn knockdown (Figure 1). Since some previous studies indicated that murine Siglec-1 or human Siglec-H interacts with DAP12 to attenuate IFN responses [14,15,39,40], we explored the interaction between poSn and DAP12 during PRRSV infection. We first observed the co-localization of poSn and DAP12 during viral infection (Figure 2A).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Siglec-G is reported to be induced and exploited by RNA viruses to inhibit retinoic acid-inducible gene-I (RIG-I)-mediated type I IFN production [13]. Siglec-H is demonstrated to negatively regulate IFN-α production in response to murine cytomegalovirus infection in vitro and in vivo [14]. Murine Siglec-1 has been recently shown to inhibit IFN responses through impairing tank binding kinase 1 (TBK1)-interferon regulatory factor (IRF)-3 pathway during vesicular stomatitis virus (VSV) infection [15].…”
Section: Introductionmentioning
confidence: 99%
“…Even if genetic predisposition, mainly represented by DQ2 or DQ8 HLA alleles, plays a key role in the pathogenesis of celiac disease (CeD), only a small fraction of individuals with such a susceptibility develop the disease, implying the presence of additional risk factors (Kupfer & Jabri, ). Viral infections have been linked to several autoimmune diseases including multiple sclerosis, type I diabetes as well as systemic lupus erythematosus and CeD itself (Ercolini & Miller, ; Schmitt et al, ). However, studies so far failed to provide mechanistic evidence for the link between viral infections and CeD, focusing mainly on epidemiological data (Abadie, Sollid, Barreiro, & Jabri, ).…”
Section: Main Textmentioning
confidence: 99%